Leverage Sebagai Pemoderasi Pada Pengaruh Intellectual Capital Terhadap Profitabilitas - Ubaidillah, Moh. (SUSTAINABLE, 2023)
This study aims to determine the effect of intellectual capital on profitability with leverage as a moderating variable. The population of this study are banking companies listed on the Indonesia Stock Exchange (IDX). The sample of this study is the financial data of banking companies in 2019-2022 with the sampling technique is perpusive sampling which results in 43 companies and 172 financial data of banking companies. The data analysis technique uses linear regression with SPSS 24. The results of this study indicate that intellectual capital and leverage have a significant positive effect on profitability. Furthermore, leverage is able to moderate the effect of intellectual capital on profitability.